Characterisation of 3D‐GaN/InGaN core‐shell nanostructures by transmission electron microscopy. Issue 3 (10th March 2014) - Griffiths, Ian; Cherns, David; Wang, Xue; Wehman, Hergo‐Heinrich; Mandl, Martin; Strassburg, Martin; Waag, Andreas
Abstract: Transmission and scanning electron microscopy have been used to characterise GaN/InGaN 3D nanostructures grown on patterned GaN/sapphire substrates by metal organic vapour phase epitaxy (MOVPE). It has been found that the growth of well ordered arrays of such nanostructures, containing multiple quantum wells on non‐polar side‐facets, can be achieved with a low density of defects. Growth changes and surface morphology play a major role in the nucleation of any defects present. The nanostructure morphology has been investigated and differing growth rates on adjacent facets studied. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)